2015
DOI: 10.1039/c4an01593b
|View full text |Cite
|
Sign up to set email alerts
|

A fiber-optic sorbitol biosensor based on NADH fluorescence detection toward rapid diagnosis of diabetic complications

Abstract: Accumulation of sorbitol in the tissue is known to cause microvascular diabetic complications. In this paper, a fiber-optic biosensor for sorbitol which is used as a biomarker of diabetic complications was developed and tested. The biosensor used a sorbitol dehydrogenase from microorganisms of the genus Flavimonas with high substrate specificity and detected the fluorescence of reduced nicotinamide adenine dinucleotide (NADH) by the enzymatic reaction. An ultraviolet light emitting diode (UV-LED) was used as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 22 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…The optical transducer can monitor either the absorption change at 340–360 nm, or the fluorescence emission change at 450 nm, and the signal is then correlated to the concentration of the target analytes. Biosensors built on this principle have been developed for the monitoring of glucose, cholesterol or l -amino acids [97], glucose-6-phosphate [98], sorbitol [99], glutamate [100], pyruvate or l -lactate. In a different approach, a fluorescent inhibitor is used to specifically bind to an enzyme in the presence of a specific cofactor.…”
Section: Enzyme-based Biosensorsmentioning
confidence: 99%
“…The optical transducer can monitor either the absorption change at 340–360 nm, or the fluorescence emission change at 450 nm, and the signal is then correlated to the concentration of the target analytes. Biosensors built on this principle have been developed for the monitoring of glucose, cholesterol or l -amino acids [97], glucose-6-phosphate [98], sorbitol [99], glutamate [100], pyruvate or l -lactate. In a different approach, a fluorescent inhibitor is used to specifically bind to an enzyme in the presence of a specific cofactor.…”
Section: Enzyme-based Biosensorsmentioning
confidence: 99%
“…A FOBS for sorbitol was constructed by immobilizing sorbitol dehydrogenase on an optical fiber. 329 In the presence of NAD + , the enzymatic oxidation of sorbitol leads to a reduction of NAD + to form blue fluorescent NADH. Sorbitol can be assayed in the 1.0−1000 μM concentration range.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…The major benefit offered by a fluorescence-based biosensors is their greater selectivity as every molecule shows its characteristic fingerprint spectrum (Strianese et al 2012). For instance, the conversion of NAD + to NADH was employed to detect a diabetic biomarker sorbitol, where the fluorescence intensity of NADH is correlated with the quantification of sorbitol (Gessei et al 2015) (The schematic representation has been shown in Fig. 3b).…”
Section: Optical Biosensorsmentioning
confidence: 99%